Policy Strategy of Financial Report Quality and Ecosystem Mechanism in Preparation of Government Financial Reports - Sodyom, Athira; Panmarerng, Kalyaporn (Arts of Management Journal, 2024)
This research aimed to propose policy strategies for enhancing the quality of public financial statements. It employed a qualitative research methodology. The population and sample consisted of experts with specialized knowledge in public accounting work, divided into three groups of three people, totaling nine people: Group 1 comprised public accountants; Group 2 included officials from the Comptroller General’s Department for supervising public accounts; and Group 3 consisted of the officials from the Office of the Auditor General of Thailand responsible for inspecting public financial statements. The sample selection was carried out using the Purposive Sampling method. The research instrument utilized was a structured interview with open-ended questions. The results of the research identified two key policy strategies for enhancing the quality of public financial statements: (1) Strategy 1 involves strengthening the upskilling and reskilling of public accountants, which includes three development modules: Module 1 for basic level public accountants, Module 2 for mid-level public accountants with less than ten years of work experience, and Module 3 for senior public accountants with ten years or more of work experience. Additionally, (2) Strategy 2: The creation of ecosystem mechanisms facilitating success for the quality of financial statements consists of thirteen factors: (1) clear policy, (2) well-defined plan and strategy, (3) visionary and supportive executives, (4) sufficient budgetary support, (5) an organizational structure conducive to effective work, (6) specialized professional manpower, (7) systematic work procedures, (8) standardized practices for government accountants, (9) robust information system, (10) rules, regulations, and guidelines facilitating and protecting public accountants, (11) work-skills and competency-building initiatives, (12) coaching and mentoring system, and (13) monitoring and evaluation framework for assessing work performance.